Рослинна сировина - паливо для енергетичних засобів машинно-тракторних агрегатів - Вороновський, Ігор Богданович; Вороновский, Игорь Богданович; Voronovskyi, Ihor (ТДАТУ, 2013)
UK: Розглядається вирішення проблеми енергетичної безпеки країни шляхом заміни нафтопродуктів, які використовуються мобільними енергетичними засобами МТА, паливно-мастильними матеріалами виготовленими з рослинної сировини. EN: In the article the decision of problem of power safety of state is examined by the way of replacement of naphtha which are used by mobile energy, by oil petrol materials made from a digester. Recently, the urgency is high energy dependence. For the agricultural sector, this problem is in short supply and high cost of petroleum products, which are used for the operation of mobile power (tractors, combines, etc.). Given that Ukraine provides its petroleum needs for 85...90% through imports and the price on the world market for it is growing, it makes us look for alternative sources of energy. One of them – biofuels - various petroleum substitutes made from plant materials. Therefore, we believe that it is necessary in this area to use castor seeds. Attractiveness of business related to the production and processing of castor currently has only two conditions - the potential of natural and southern Ukraine, and the significant market demand in castor oil. As a result, farmers do not feel the economic interest in the production of castor. This requires the study plans of goods, which is oriented to guarantee its implementation and eliminate the risk of.
Keywords: рослинна сировина; біопаливо; дизельне паливо